2013
DOI: 10.3174/ajnr.a3677
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Proton MR Spectroscopy for Differentiating Typical and Atypical Primary Central Nervous System Lymphomas from Tumefactive Demyelinating Lesions

Abstract: BACKGROUND AND PURPOSE: It may be challenging to differentiate primary CNS lymphomas, especially primary CNS lymphomas with atypical MR features, from tumefactive demyelinating lesions by the use of conventional MR. This study aimed to investigate the usefulness of 1 H-MR spectroscopy for making this discrimination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 26 publications
1
23
0
Order By: Relevance
“…There are few reports in the literature regarding the characteristic 1 H-MRS pattern of PCNSL. An increase in lipid resonances has been reported as the most specific finding for PCNSL on 1 H-MRS [12,[14][15][16]. (Table 3) Harting et al [17] found significantly higher lipid peaks in solid PCNSL than in solid low-and high-grade astrocytomas.…”
Section: Discussionmentioning
confidence: 94%
“…There are few reports in the literature regarding the characteristic 1 H-MRS pattern of PCNSL. An increase in lipid resonances has been reported as the most specific finding for PCNSL on 1 H-MRS [12,[14][15][16]. (Table 3) Harting et al [17] found significantly higher lipid peaks in solid PCNSL than in solid low-and high-grade astrocytomas.…”
Section: Discussionmentioning
confidence: 94%
“…[3940] TDLs on MRS show as follows:[4142] elevation of choline (Cho) peak, reduction of N-acetylarginine (NAA) peak, and most of the lesions have some elevation of lactate peak [Figure 6a]. …”
Section: Auxiliary Examinationmentioning
confidence: 99%
“…[3943] Hyperperfusion is usually observed in glioma [Figure 7a and 7b], which does not occur in TDLs [Figure 7c and 7d]. [24]…”
Section: Auxiliary Examinationmentioning
confidence: 99%
See 2 more Smart Citations